1998
DOI: 10.2214/ajr.171.6.9843311
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of specimen radiography for core needle biopsy of noncalcified breast masses.

Abstract: OBJECTIVE. Our objectivewas to determinethe predictivevalueof specimenradiography for large core (14-gauge) needle biopsy of noncalcified breast masses. SUBJECTS AND METHODS. Eighty-four biopsiesof 83 breastmassesyielded 403specimens. Specimens showing dense material on specimen radiography were predicted to be diagnostic;specimensshowingintermediate-or low-densitymaterial were predictedto be nondiagnostic. Specimenradiographicand histopathologic findingswere correlatedfor each specimen using vital dyes to mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…When microcalcifications detected in mammography are sampled, specimen radiography can ensure that sufficient amounts of microcalcification have been removed via cutting needle biopsy or vacuum biopsy; however, in US-guided biopsy, it is more difficult to demonstrate that the sample is sufficient [13,14]. US-guided biopsy is a technically easy procedure, and generally provides reliable sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When microcalcifications detected in mammography are sampled, specimen radiography can ensure that sufficient amounts of microcalcification have been removed via cutting needle biopsy or vacuum biopsy; however, in US-guided biopsy, it is more difficult to demonstrate that the sample is sufficient [13,14]. US-guided biopsy is a technically easy procedure, and generally provides reliable sampling.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially in non-solid masses and small lesions, demonstrating whether or not a sufficient sample has been obtained is not easy. If a lesion is easily seen on mammography, post-biopsy mammography control is capable of demonstrating that the sample has been obtained from the right region [13,14]. However, in 14-gauge needle biopsies, changes are generally not sufficient to yield marked findings in mammography relating to the breast tissue and the non-calcified lesion.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Specimen radiography can provide evidence that tissue was retrieved from the appropriate site during percutaneous biopsy of calcification lesions 17,18 but is less helpful for masses. 19 Postbiopsy mammography may reveal changes at the biopsy site, 20,21 but there is often no substantial alteration in the target lesion, particularly if the biopsy is performed with a smaller tissue acquisition device such as the 14-gauge automated needle. 22 Imaging-histologic correlation, therefore, plays an important role in percutaneous breast biopsy because of the limitations of other methods of confirming lesion sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Venta et al (29) describe focal fibrosis as typically manifesting as a circumscribed mass: marginal spiculation should be considered discordant with a diagnosis of fibrosis on the basis of findings of core-needle biopsy. Further, Berg et al (30) reported that 22 (32%) of 68 core specimens showing only focal fibrosis had actually missed the lesion and that such a result was particularly problematic in dense breast tissue. As such, this patient chose bilateral mastectomy out of her understanding of the limitations of imaging and even core-needle biopsy in depicting both current and any subsequent disease.…”
Section: Discussionmentioning
confidence: 99%